Protection Against Unauthorized Access of Mobile Devices When Using the BYOD Concept - Kornienko, A. A.; Kornienko, S. V.; Razzhivin, N. S. (Automatic control and computer sciences, 2024)
The problems of using mobile devices in the work process of an organization when applying the BYOD concept are analyzed. An adapted methodology for assessing security threats is proposed for BYOD concepts. As a supplement to the traditional approach to building a system for ensuring information security in a corporate information system based on BYOD, a software tool for controlling unauthorized access to mobile devices is developed and tested.